Effect of Holes Arrangement on Effusion Cooling Performance - Muwafag Sh. Alwan; Reyadh Ch. Al-Zachary (Engineering and Technology Journal, 2014)
The present work concentrates on the experimental investigation of effusion cooling performance for different whole pitch ratios. The film cooling effectiveness and local heat transfer coefficient for difference jet holes arrangement have been investigated on a flat plate at three blowing ratios (0.5,1.0 and 1.5) at Reynolds number based upon hole diameter and hot main stream velocity is (6000). The investigations were done by using a single test transient IR the rmography technique. Three models of staggered holes arrangement are investigated. Each model is provided with seven rows of holes. The holes diameter (D) is 4mm, the longitudinal distance (X) are 8D, 10D and 12D respectively, and the span wise distance(S) between two neighboring holes are 7D.The attitude of the holes is fixed at inclination angle (θ= 30º). The experimental investigation shows that the thermal performance decreases as the pitch ratio (X/D) increases for all blowing ratios, and the film cooling effectiveness decreases as the blowing ratio increases for all the three models.